THE LEGAL STUDY OF ALLEGED MALPRACTICES IN THE PROCESS OF MAKING AUTHENTIC DEEDS OF SALE AND PURCHASE - Tjandraningsih, Dewi (Jurnal Pembaharuan Hukum, 2023)
The notaries who are suspected of committing acts of malpractice in their official duties, either intentionally or through negligence and violating Law No. 2 of 2014 concerning the Position of Notaries, can result in losses for the parties and can complain to the Notary Honorary Council and the police. This research aims to determine and analyze the authority of notaries in making authentic deeds, and legal certainty for the parties in an authentic deed. The research method uses normative legal research with a legislative approach that uses legal sources with library methods which are then analyzed to obtain a conclusion. The results and conclusions of the research are that a Notary is a public official who has the authority to make an authentic deed based on attribution or Law No. 2 of 2014, apart from that, authentic deeds are required by statutory regulations in order to create legal certainty, order and legal protection, so that the meaning of legal certainty will be properly actualized if the parties understand what is the purpose of the deed.